PENGGUNAAN MODEL PEMBELAJARAN DISCOVERY LEARNING PADA MATERI MUBTADA KHABAR KELAS VII MTs AL-MUSYAWARAH LEMBANG - Khoirunnisa, Fina (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2019)
This research is motivated by the problems experienced by students in learning material mubtada khabar preachers who are difficult to understand in their implementation. The method used by the teacher is less effective. In this situation resulted in students tend to be more passive in teaching and learning activities. However, different conditions exist in Al-Musyawarah Lembang MTs, where students are very enthusiastic about the preaching material, because of the teacher's efforts to apply the discovery learning model. The purpose of this study was to describe the discovery learning model of the seventh-grade students of Al-Musyawarah Lembang preaching material mubtada khabar. Based on the results of the study: planning on the material of mubtada khabar in using the discovery learning model with the 2013 curriculum syllabus, the process on the material of Khubtada Khabar in using the discovery learning model students can focus on during the learning process, so students can apply the material quite well, evaluating the material mubtada khabar in using discovery learning models with assessment techniques namely oral and written tests.